Personality processes mechanisms by which personality traits get outside the skin.[article]. - Hampson, Sarah E.
It is time to better understand why personality traits predict consequential outcomes, which calls for a closer look at personality processes. Personality processes are mechanisms that unfold over time to produce the effects of personality traits. They include reactive and instrumental processes that moderate or mediate the association between traits and outcomes. These mechanisms are illustrated here by a selection of studies of traits representing the three broad domains of personality and temperament: negative emotionality, positive emotionality, and constraint. Personality processes are studied over the short term, as in event-sampling studies, and over the long term, as in lifespan research. Implications of findings from the study of processes are considered for resolving issues in models of personality structure, improving and extending methods of personality assessment, and identifying targets for personality interventions. - (from the author)
Keywords: Personality assessment; Negative emotionality; Positive emotionality; Constraint; Mediation; Moderation; Social cognition